PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUKARELA LAPORAN TAHUNAN - Ula Restu Rafifah; Dwi Ratmono (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of corporate governance mechanisms like independent board of commissioners, board of commissioners who have the capability of accounting or business, board commissioners meetings, size board of commissioners, independent audit committee, audit committee who has the capability of accounting or business, audit committee meetings, quality auditor, and institutional ownership on  voluntary disclosure. Profitability and  firm size used as control variable.The population in this study are manufacturing companies listed in Indonesia Stock Exchange in 2010, 2011, 2012, and 2013. The sampling method in this research is purposive sampling. Sampled companies there are 43 companies with a total number of samples in this study were 172 data. Then, there are 12 samples that include outlier should be excluded from samples of observation. So, the final amounts of the sample are 160 data. Multiple regression used to be analysis technique.The results showed that, only board of commissioners meetings that have a significant influence on voluntary disclosure with the positive direction, which is consistent with the hypothesis, while other variables results show inconsistent with the hypothesis. Independent board of commissioners, independent audit committee, and audit committee who has the capability of accounting or business have significant influence on voluntary disclosure, but with a negative direction. Board of commissioners who have the capability of accounting or business, size of the board of commissioners, audit committee meetings, quality auditors, and institutional ownership has no influence on voluntary disclosure.